Kontrol Kualitas Kadar Air Laut Menggunakan Fuzzy LogicUntuk Habitat Ikan Kerapu - Anizar Indriani; Marhalim Fajri (Universitas Negeri Padang, 2019)
The quality of the seawater content for the grouper fish habitat is very influential in the grouper fish development process. Seawater quality for grouper fish habitat depend on temperatur, salinity, acidity (pH), and turbidity of seawater. The quality of seawater can be control by circulation in and out of seawater in the fish pond. This cycle is required to maintain the desired quality of seawater at temperatur 24ºC- 31ºC, salinity 30-33 ppt, dissolved oxygen> 3,5 ppt, and pH 7,5-8,3. In previous studies seawater control systems have been carried out in the form of controls temperatur and pH quality. Other components quality of sea water such as salinity and turbidity due to fish food also influence seawater quality for grouper fish habitat. Component control of sea water in this paper include microcontroller, pump sea water, fresh water pump, sensor and etc. In this paper we are focus on the controlling sea water quality to maintain the quality of grouper fish pools consisting of temperatur, salinity, acidity (pH), and turbidity of seawater. Input this data and the pH of the water read by the sensor will be processed with fuzzy logic to adjust the working of the salt water pump and the freshwater pump until it reaches the setpoint value. Turbidity and temperatur control using the ON-OFF system. The results show that of testing the sea water quality of control system using fuzzy logic in accordance with the calculation of mathematical defuzzyfication with an error of 0%. The values of salinity control system 31,14-32,98 PPT, pH 7,78-8,.2, temperatur 27ºC-29,98ºC, and turbidity level 9,90-14,85 NTU.